Development of a Solar Home in Middle East: A Review - Elina Mohd Husini; Nor Haslina Jaafar; Sharma Rao Balakrishnan; Wan Zakiah Wan Ismail; Fadli Arabi (Universiti Sains Islam Malaysia, 2024)
The exponential growth of the population and development comes in hand with excessive use of natural resources which leads to the depletion of the non-renewable material. The main goal of this Solar Decathlon Solar Home competition is to select the best home, whichcan be assembled within 10 days in the desert climate. The solution of four issues withcapacities and technologies are strategized to implement the benefit of the inhabitants of the Middle East region such as sobriety, innovation and mobility. The main objectives of this study are to describe the design philosophy, highlight the exclusive experimental analysis on thermal and sensor which embed the energy efficient and sustainability. The added value ofIslamic perspective of 'Mizan' and 'Sakinah' which mean balanced home and tranquillityare emphasizing the application of balance need for human and nature. The results showed the conductivity of plant waste material known as oil palm trunk is a medium of a heat transport and thermal insulator during high temperature while the innovative sobriety solution is achieved through wind and sandstorm sensor. A conclusion was drawn that the engineering of green product is performed the optimum human comfort in the dwelling of desert area,while from a social aspect, the principleof privacy protection is essential through the planningof a space in the solar home.